Implementation of Access and Benefit Sharing in The Bahamas: A Precautionary Tale - Krista Sherman; Craig Dahlgren; Charlotte Dunn; Diane Claridge; Nicholas Higgs (Conservation)
Biodiversity is incredibly important for the myriad ecosystem services it provides, especially for coastal nations such as The Bahamas. However, the newly implemented access and benefit sharing (ABS) regime is undermining scientific research, which is essential to effectively manage and conserve the country’s biodiversity. Key challenges include a poorly drafted legislation with punitive damages (financial and criminal), an overly bureaucratic and dysfunctional permitting process, and cost-prohibitive registration fees that are unsustainable for most researchers and organizations. As a result, the newly implemented ABS regime is driving the demise of academic and conservation research needed to protect the country’s biodiversity, diverting funding away from The Bahamas, jeopardizing relationships with the international scientific community, reducing its capacity to advance science innovation, and impeding much needed experiential learning opportunities for Bahamian students and professionals. A critical solution under the current permitting regime is the need to distinguish between commercial and non-commercial research in the regulatory framework and provide separate accommodations for the same. Furthermore, countries that consider establishing national ABS frameworks are advised to thoroughly engage with all relevant stakeholders through a transparent and consultative process during ABS design and implementation. This will help to ensure that the resulting legislation and policies do not unnecessarily obstruct the research needed for biodiversity conservation and natural resource management.